PENDAMPINGAN KEBERLANGSUNGAN USAHA UMKM GULA AREN DALAM MENDUKUNG PENCAPAIAN SUSTAINABILITY DEVELOPMENT GOALS (SDGs) - Nurfitriana, Annisa (Jurnal Berdaya Mandiri, 2023)
Palm trees are one of the natural resources in Majalengka. its availability needs to be maintained by all parties so that the palm processing business can have an impact on economic, environmental, and social aspects. However, the limited number of trees that are decreasing, decreasing interest in doing business, and limited human resource capabili-ties are obstacles for MSME actors. The implementation method used to carry out the service is by conducting surveys, providing equipment and training, and providing assis-tance and evaluation. The result of this service is that the first palm sugar SMEs in Maja-lengka, processed production is increasing and is of higher quality. In addition, MSME actors can manage finances so that there is an increase in turnover and the sustain-ability of MSMEs is maintained. This supports the achievement of the economic aspect. Second, MSME actors are closer to neighbors and families in supporting efforts to support social aspects. Third, MSME actors are more likely to maximize production amid limited natural resources so that they can support the achievement of SDGs in environmental aspects. Keywords: SMEs, Sustainability Development Goals